Analysis of Cyber Security Challenges in Bandar Lampung: Impact on Digitalization, Religion, and Society - Choiriyati, Sri; Asniar, Immawati; Meiranti, Mike; Rupawan, Ratu Sukma (Jogjakarta Communication Conference (JCC), 2025)
This study aims to identify and analyze the challenges faced in cybersecurity in Bandar Lampung, focusing on its impact on the digital sector, religion, and society. This study uses a qualitative approach through interviews with a number of experts and practitioners in the field of cybersecurity, as well as related literature studies. The results of the study indicate that cybersecurity in Bandar Lampung faces various problems, such as lack of public awareness, lack of clear regulations, and challenges in protecting personal data and digital transactions. This study also found that cyber threats have the potential to disrupt religious activities and social interactions in society. In conclusion, increased awareness, education, and cooperation between the government, religious institutions, and society are needed to overcome these challenges.